FANCD2 Maintains Fork Stability in BRCA1/2-Deficient Tumors and Promotes Alternative End-Joining DNA Repair - Kais, Zeina; Rondinelli, Beatrice; Holmes, Amie; O’Leary, Colin; Kozono, David; D’Andrea, Alan D.; Ceccaldi, Raphael (Cell reports (Cambridge), 2016)
BRCA1/2 proteins function in homologous recombination (HR)-mediated DNA repair and cooperate with Fanconi anemia (FA) proteins to maintain genomic integrity through replication fork stabilization. Loss of BRCA1/2 proteins results in DNA repair deficiency and replicative stress, leading to genomic instability and enhanced sensitivity to DNA-damaging agents. Recent studies have shown that BRCA1/2-deficient tumors upregulate Polθ-mediated alternative end-joining (alt-EJ) repair as a survival mechanism. Whether other mechanisms maintain genomic integrity upon loss of BRCA1/2 proteins is currently unknown. Here we show that BRCA1/2-deficient tumors also upregulate FANCD2 activity. FANCD2 is required for fork protection and fork restart in BRCA1/2-deficient tumors. Moreover, FANCD2 promotes Polθ recruitment at sites of damage and alt-EJ repair. Finally, loss of FANCD2 in BRCA1/2-deficient tumors enhances cell death. These results reveal a synthetic lethal relationship between FANCD2 and BRCA1/2, and they identify FANCD2 as a central player orchestrating DNA repair pathway choice at the replication fork. [Display omitted] •Loss of FANCD2 and BRCA1/2 is synthetic lethal•FANCD2 maintains fork stability in BRCA1/2-deficient cells•FANCD2 promotes alternative end joining (alt-EJ)•FANCD2 overexpression confers resistance to PARP inhibitors Kais et al. show that BRCA1/2-deficient tumors have a compensatory increase in FANCD2 activity. FANCD2 stabilizes stalled replication forks and promotes alternative end joining (alt-EJ) in BRCA1/2-deficient tumors. Loss of FANCD2 in these tumors results in severe DNA repair defects and enhanced cell death.